2009
DOI: 10.2139/ssrn.1489371
|View full text |Cite
|
Sign up to set email alerts
|

Does Gender Matter in Bank-Firm Relationships? Evidence from Small Business Lending

Abstract: In this paper we study the relevance of the gender of the contracting parties involved in lending. We show that female entrepreneurs face tighter access to credit, even though they do not pay higher interest rates. The effect is independent of the information available about the borrower and holds if we control for unobservable individual effects. The gender of the loan officer is also important: we find that female officers are more risk-averse or less self-confident than male officers as they tend to restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 72 publications
1
65
1
Order By: Relevance
“…The results of Belluchi, Borisov and Zazzaro (2010), who examined the gender-based discrimination in bank financing in the Italian market using credit fie data from 7 800 small businesses, show that female entrepreneurs are faced with some strict conditions in the loan contract: higher collateral, lower credit limits and quicker maturity of the loan. They did not find any discrimination in the pricing of the loans and it suggests that similar interest rates are available for both men and women entrepreneurs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The results of Belluchi, Borisov and Zazzaro (2010), who examined the gender-based discrimination in bank financing in the Italian market using credit fie data from 7 800 small businesses, show that female entrepreneurs are faced with some strict conditions in the loan contract: higher collateral, lower credit limits and quicker maturity of the loan. They did not find any discrimination in the pricing of the loans and it suggests that similar interest rates are available for both men and women entrepreneurs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Generally, research has demonstrated the impact between a smaller number of women business angels and the gender-gap in angel funding rates and a tendency for women angels to refuse financing to women entrepreneurs, although they are more likely to seek funding from other women (Becker-Blease and Sohl 2007). Other scholars have explored loan-officers' decision-making in the UK and Italy, suggesting that their sex influences lending decisions (Bellucci, Borisov, and Zazzaro 2010;Carter et al 2007;Wilson et al 2007).…”
mentioning
confidence: 99%
“…Additional evidence on gender discrimination in Italian small business lending is provided by Bellucci, Borisov and Zazzaro (2009). Buvinic andBerger (1990) andFletschner (2009) show that women keep being more credit-rationed than men by MFIs.…”
mentioning
confidence: 99%